Fatores externos e genotípicos no crescimento diferencial da plúmula em relação ao comprimento do coleóptilo de plântulas de milho - Lopes, Camila Aparecida (2016)
The physiological potential evaluation of lots in the certification process is usually performed by the germination test, by the normal seedlings distinction obtained at the final test. However, in some tests, delays are observed in the growth of shoots’ structures seedlings, which leads to consider them abnormal seedlings. This situation adversely affects the test results, but does not necessarily reflect the lot’s behavior in the field. It was goal in this study to investigate the effect of genotype, water, light, temperature and chemical treatment on the plumule differential growth in relation length of the maize seedling coleoptile. The experiments were conducted at the Seed Analysis Laboratory and Plant Anatomy Laboratory at the Federal University of Lavras. Two simple hybrid seeds and their reciprocal with slow growth characteristic of the shoot were evaluated by germination on paper and sand, pericarp hist ologic analysis, lignin histochemistry analysis on the coleoptile wall and expression of α-amylase, β-amylase and endo-β-mannanase. There are differences between maize genotypes as regards the plumule initial growth in relation to the coleoptile, especially in the absence of light on germination test. These differences are not observed at the seven days after sowing. The water availability, the optimal temperature range and chemical treatment with Deltamethrin not affect the response of the hybrid in relation to differential growth of plumule. The pericarp thickness, lignin presence and differences in the enzymes activity of different genotypes are not related to changes in length plumule/coleoptile during maize seed germination test.